Evaluating the influence of monetary and non-monetary rewards in enhancing employee performance - Geetha Kaurr Chandi, Stevender Singh (2025)
This research studies the influence of both monetary and non-monetary rewards on employee performance in Malaysia. Even though, monetary and non-monetary rewards like salaries, and bonuses has a vital role in satisfying extrinsic needs, they may not necessarily provide long-term employee motivation which leads to favourable performance. In contrast, non-monetary incentives, which encompass recognition and flexible working hours, satisfy intrinsic needs and enhance job satisfaction, employee retention, and productivity. Employing Herzberg’s Two-Factor Theory as a conceptual framework, this study highlights deficiencies within current reward systems, especially concerning the application of flexible working hours. The method of research adopted was quantitative by collecting data with the use of strategically developed questionnaires which was later on circulated across carious sectors in Malaysia. This research also employs descriptive statistical methods, along regression analyses, to investigate the relationship between the independent variables that are salaries, bonuses, recognition, and flexible working hours and dependent variable which is employee performance. Furthermore, this research intends to raise the issue of deficiency in current literature by highlighting a gap that is the significance of flexible working hours as a unique form of reward. Upon the adoption of these findings with the application of Herzberg’s theoretical framework, this study can contribute significantly by providing insights for employers today to come up with a comprehensive reward system that harmonize employee satisfaction with organizational objectives.